SiO2@C composite based on surface in-situ modification and preparation method and application thereof
Patent Information
- Application Number
- CN202510419069.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]石墨作为钾离子电池负极材料时,面临首次库伦效率低(约71%)、倍率性能差(如500 mA g–1下容量仅100.1 mAh g–1)、循环稳定性不足(50次循环后失效)等问题
[0032]1) The SiO2@C composite material provided by the present invention, through the SiO2 nano-coating formed in situ on the surface of the carbon matrix, not only significantly optimizes the characteristics of its SEI layer, but also greatly improves the adsorption and desorption capacity of the material for potassium ions. The adsorption energy of the composite material for potassium ions is -2.514 eV and the diffusion kinetic energy barrier is 0.035 eV.
Smart Images

Figure CN122916121A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a Si-C composite material, specifically to a SiO2@C composite material based on in-situ surface modification, its preparation method, and its application, belonging to the field of electrochemical energy storage technology. Background Technology
[0002] When graphite is used as an anode material in potassium-ion batteries, it faces challenges such as low initial coulombic efficiency (approximately 71%) and poor rate performance (e.g., at 500 mA g). –1 The capacity is only 100.1 mAh g. –1 Problems include insufficient cycle stability (failure after 50 cycles). The main reasons include: 1) A thick and unstable SEI layer: Traditional KPF6-based electrolytes continuously decompose on the graphite surface, forming an organic-rich SEI that hinders potassium ion diffusion and increases interfacial impedance; 2) Slow potassium ion kinetics: The diffusion barrier for potassium ions intercalation / deintercalation between graphite layers is high, approximately 99.8 kJ•mol. -1 This leads to sluggish reaction kinetics; 3) Solvent co-intercalation and side reactions: Electrolyte solvent molecules co-intercalate with potassium ions into the graphite layer, causing structural peeling and capacity decay.
[0003] Existing technologies, such as high-concentration electrolytes and artificial SEI layers, suffer from drawbacks such as high cost, complex processes, or poor compatibility. Therefore, the market urgently needs a low-cost, high-efficiency graphite surface modification technology to simultaneously optimize SEI properties and potassium ion transport kinetics. Summary of the Invention
[0004] To address the problems existing in the prior art, the first objective of this invention is to provide a SiO2@C composite material based on in-situ surface modification. This composite material, through the in-situ formation of SiO2 nano-coating on the surface of a carbon matrix, not only significantly optimizes the SEI layer characteristics but also greatly improves the adsorption and desorption capacity of the material for potassium ions. The adsorption energy of the composite material for potassium ions is -2.514 eV, and the diffusion kinetic energy barrier is 0.035 eV.
[0005] The second objective of this invention is to provide a method for preparing SiO2@C composite materials based on in-situ surface modification. This method uses a silane coupling agent as a silicon source, and the silicon source is uniformly grafted onto the surface of a carbon matrix that has undergone surface oxidation treatment by an impregnation method. Then, a uniform silicon dioxide thin film layer is formed in situ on the surface of the carbon matrix by programmed temperature sintering, thereby optimizing the surface interface dynamics of the carbon material.
[0006] The third objective of this invention is to provide an application of surface-modified SiO2@C composite materials for the preparation of potassium-ion secondary batteries. Based on the excellent properties of the aforementioned SiO2@C composite material, using it as the anode material in potassium-ion secondary batteries can significantly improve a series of performance characteristics, including initial coulombic efficiency, rate performance, cycle stability, and potassium-ion diffusion kinetics. Testing showed that its capacity retention rate can reach 90% after 600 cycles, and even when the current density is increased tenfold, its capacity retention rate still reaches 61.8%, exhibiting excellent electrochemical performance.
[0007] To achieve the above-mentioned technical objectives, this invention provides a method for preparing SiO2@C composite materials based on in-situ surface modification, comprising: oxidizing the surface of carbon material and cleaning it to obtain a carbon matrix; dissolving a silane coupling agent and a dispersant in a mixed solvent, adding the carbon matrix to perform a grafting reaction, and after the reaction, performing solid-liquid separation and washing to obtain a composite material precursor; drying the composite material precursor and then performing in-situ SiO2 growth using a programmed temperature rise method to obtain the final product; wherein the volume-to-mass ratio of the silane coupling agent to the carbon material is 5~10:1 mL / g.
[0008] As a preferred embodiment, the volume-to-mass ratio of the silane coupling agent to the carbon material is 8:1 mL / g.
[0009] The preparation method provided by this invention first performs surface oxidation treatment on carbon materials to generate an appropriate amount of surface oxygen-containing functional groups, which facilitates the subsequent grafting of silane coupling agents. Then, a temperature-programmed method is used to induce the in-situ growth of the silane coupling agent grafted onto the carbon material surface into a SiO2 layer. The SiO2 layer can regulate the interfacial kinetics of the graphite anode, which can not only enhance the K... + The transport kinetics reduce irreversible depletion of potassium ions and generate abundant active sites, resulting in relatively high potassium adsorption energy and low potassium migration barrier. It is important to note that the volume-to-mass ratio of silane coupling agent to carbon material must be performed according to the above requirements. If the amount of silane coupling agent added is too low, the coating effect will be poor and the cycle stability will be insufficient. If the amount of silane coupling agent added is too high, the coating layer will be too thick, reducing electronic conductivity.
[0010] As a preferred embodiment, the carbon material is at least one selected from graphite, graphene, carbon nanotubes, and hard carbon. More preferably, the carbon material is graphite.
[0011] As a preferred embodiment, the surface oxidation treatment is performed by volumetric impregnation of an oxidant, the process of which is as follows: under stirring conditions at 50~70℃, the carbon material is completely impregnated in the oxidant, and the oxidation treatment lasts for 2~6 hours.
[0012] The surface oxidation treatment provided by this invention must be strictly performed in accordance with the above requirements. The original carbon material can be induced to generate hydroxyl groups (-OH) on its surface by an oxidant. The hydrolyzed silane coupling agent can combine with the oxygen atoms on the surface of the treated carbon material, thereby further chemically grafting onto the carbon material. If the degree of surface oxidation is too low, the oxidation effect will not be achieved and enough hydroxyl groups will not be generated. If the degree of oxidation is too high, it will further damage the structure of the carbon material and affect its electrochemical performance.
[0013] As a preferred embodiment, the oxidant is hydrogen peroxide with a concentration of 1-3 mol / L.
[0014] As a preferred embodiment, the mass-to-volume ratio of the carbon material to hydrogen peroxide is 1:10~30 g / mL.
[0015] As a preferred embodiment, the silane coupling agent is at least one selected from KH550, KH560, KH580, and A-1100. More preferably, the silane coupling agent is KH550.
[0016] As a preferred embodiment, the dispersant is at least one of PVP, PVA, and PMMA.
[0017] As a preferred embodiment, the mixed solvent is composed of anhydrous ethanol and deionized water in a volume ratio of 1 to 3:1. More preferably, the volume ratio of anhydrous ethanol to deionized water in the mixed solvent is 2:1.
[0018] This invention utilizes a mixed solvent of ethanol and deionized water to precisely control the polarity of the solution, thereby influencing the surface modification effect of materials. This mixed solvent can effectively promote the reaction of materials with other substances or the adhesion of coatings, improving the material's properties.
[0019] As a preferred embodiment, the grafting reaction is carried out under the following conditions: a temperature of 50-70°C under stirring, and a reaction time of 1-3 hours.
[0020] As a preferred embodiment, the washing process is as follows: the filter cake is washed with anhydrous ethanol until no silane is present in the washing liquid.
[0021] As a preferred option, the drying method is one of vacuum drying, oven drying, and freeze drying.
[0022] As a preferred embodiment, when the drying is performed in an oven, the conditions are: drying the material at 80~120℃ to a constant weight.
[0023] As a preferred embodiment, the in-situ growth process of SiO2 is as follows: under a protective atmosphere, the temperature is heated to 400-500°C at a rate of 1-10°C / min and held for 3-6 hours, then cooled to 250-300°C at a rate of 1-10°C / min and held for 10-20 hours, and then cooled to room temperature with the furnace.
[0024] The calcination process is one of the important steps in the in-situ growth of SiO2. By controlling different temperature treatments, the microstructure of graphite can be regulated, and the surface oxygen content can be reduced, thereby enhancing its electrical conductivity and thermal stability.
[0025] The present invention also provides a SiO2@C composite material based on in-situ surface modification, which is prepared by the method described in any one of the above methods; the SiO2@C composite material includes a carbon matrix and a SiO2 nanolayer modified on its surface; the thickness of the SiO2 nanolayer is 1~10 nm.
[0026] This invention also provides an application of SiO2@C composite material based on in-situ surface modification for the preparation of potassium-ion secondary batteries; the potassium-ion secondary battery includes a positive electrode, a negative electrode containing SiO2@C composite material, a separator, and an electrolyte; the positive electrode includes the following mass fractions: 6-8 parts active PB, 2-3 parts conductive agent, and 1-2 parts binder; the negative electrode includes the following mass fractions: 7-8 parts SiO2@C composite material, 1-2 parts conductive agent, and 1-2 parts binder.
[0027] As a preferred embodiment, the preparation process of the potassium-ion secondary battery includes:
[0028] Step S1: Mix the active PB, conductive agent and binder in NMP and stir overnight to obtain a positive electrode slurry. Then coat it onto an aluminum foil current collector, and after drying and cutting, obtain the positive electrode sheet.
[0029] Step S2: Mix the SiO2@C composite material, conductive agent and binder in an ethanol aqueous solution and stir overnight to obtain a negative electrode slurry. Then coat the slurry onto a copper foil current collector. After drying and cutting, a negative electrode sheet is obtained.
[0030] Step S3: Assemble and encapsulate the negative electrode, positive electrode, glass fiber separator, and KPF6 electrolyte to obtain the final product.
[0031] Compared with the prior art, the beneficial technical effects of the technical solution provided by the present invention are as follows:
[0032] 1) The SiO2@C composite material provided by the present invention, through the SiO2 nano-coating formed in situ on the surface of the carbon matrix, not only significantly optimizes the characteristics of its SEI layer, but also greatly improves the adsorption and desorption capacity of the material for potassium ions. The adsorption energy of the composite material for potassium ions is -2.514 eV and the diffusion kinetic energy barrier is 0.035 eV.
[0033] 2) The preparation method provided by the present invention uses silane coupling agent as silicon source, and the silicon source is uniformly grafted onto the surface of carbon matrix after surface oxidation treatment by impregnation method. Then, a uniform silicon dioxide thin film layer is formed in situ on the surface of carbon matrix by programmed temperature rise sintering, thereby optimizing the surface interface dynamics of carbon material.
[0034] 3) In the technical solution provided by the present invention, based on the excellent performance of the above-mentioned SiO2@C composite material, using it as the negative electrode material of potassium-ion secondary battery can significantly improve a series of properties such as the first coulombic efficiency, rate performance, cycle stability and potassium ion diffusion kinetics of the battery. After testing, its capacity retention rate can reach 90% after 600 cycles. When the current density is increased by 10 times, its capacity retention rate is still 61.8%, showing excellent electrochemical performance. Attached Figure Description
[0035] The present invention will be further described below with reference to the accompanying drawings and embodiments. The schematic diagrams and embodiments of the present invention are used to explain the present invention and do not constitute an improper limitation of the present invention.
[0036] Figure 1 This is a schematic diagram of the preparation and characterization process of the SiO2@C composite material provided in Example 1 and the PC composite material provided in Comparative Example 1 of the present invention;
[0037] in, Figure 1 (a) is a schematic diagram of the design and preparation process of SiO2@C composite material. Figure 1 (b) shows the transmission electron microscope (TEM) image and EDS elemental distribution map of the SiO2@C composite material. Figure 1 (c) shows the transmission electron microscope (TEM) image and EDS elemental distribution map of the PC composite material. Figure 1 (d) shows the XPS full spectrum of SiO2@C composite material and PC composite material. Figure 1 (e) is the Si2p spectrum of the SiO2@C composite material. Figure 1 (f) shows the Raman spectra of SiO2@C composite material and PC composite material;
[0038] Figure 2 The diagram shows the interface and bulk dynamics of the SiO2@C composite material ||K battery provided in Example 1 of this invention and the P-graphite ||K battery provided in Comparative Example 1.
[0039] in, Figure 2 (a) is a graph showing the distributed relaxation time data of the battery in different cycles provided in Example 1. Figure 2 (b) A graph showing the distributed relaxation time data of the battery in different cycles provided in Comparative Example 1. Figure 2 (c) is a comparison diagram of the activation energy of the negative electrode of the battery provided in Example 1 and Comparative Example 1. Figure 2 (d) is at 100 mAg -1 The graph shows the initial charging voltage change of the negative electrode of the battery provided in Example 1 and Comparative Example 1 under the charging current pulse and relaxation phase, and the measurement results of the constant current intermittent titration technique. Figure 2 (e) is a graph showing the diffusion coefficient of the negative electrode of the battery provided in Example 1 and Comparative Example 1 as a function of voltage. Figure 2 (f) is the diffusion barrier diagram of potassium ions passing through SiO2 and KF. Figure 2 (g) is a schematic diagram showing the effect of interfacial functional groups on the adsorption energy barrier of potassium ions;
[0040] Figure 3 The electrochemical performance characterization diagrams are for the half-cell systems provided in Example 1 and Comparative Example 1 of this invention.
[0041] Figure 3 (a) SiO2@C composite material and PC composite material at 50~500mAg -1 Rate performance graph within the current density range. Figure 3 (b) shows the capacity loss distribution of the half-cell system under different current densities. Figure 3 (c) is 100mAg -1 Cyclic stability of the half-cell system at current density Figure 3 (d) is the SiO2@C composite electrode at 20 mAg. -1 The dQ / dV curves for the first and second laps are shown below. Figure 3 (e) PC composite electrode at 20 mAg -1 The dQ / dV curves for the first and second laps are shown below. Figure 3 (f) represents the SiO2@C composite material in the range of 0.25~2 mVs. -1 Cyclic Fu'an curve at scan rate;
[0042] Figure 4 The SEI characterization diagrams are of the SiO2@C composite material provided in Example 1 and the PC composite material provided in Comparative Example 1.
[0043] in, Figure 4 (a) SiO2@C composite material at 50 mAg -1 In-situ XRD contour plot of charge-discharge cycles at current density. Figure 4 (b) XPS atomic ratio diagrams of different depths of the SEI layer of the negative electrode obtained from SiO2@C composite material and PC composite material. Figure 4 (c) shows the high-resolution Si2p and C1s XPS spectra of the graphite anode after cycling. Figure 4 (d) is a high-resolution transmission electron microscope image of the negative electrode obtained from the SiO2@C composite material and PC composite material after cycling. Figure 4 (e) is a 3D time-of-flight secondary ion mass spectrometry fragment reconstruction diagram of SiO2@C composite material and PC composite material;
[0044] Figure 5 Electrochemical performance diagram of the PB||SiO2@C composite material full cell provided by this invention;
[0045] Figure 5 (a) Full cells of PB||SiO2@C composite material at 200 mAg -1 Cyclic performance graph at current density Figure 5 (b) shows the rate performance of the PB||SiO2@C composite full cell. Figure 5 (c) shows the voltage curves of the PB||SiO2@C composite full cell at different current densities. Figure 5 (d) is a schematic diagram of the evolution mechanism of the negative electrode of the PB||SiO2@C composite full cell during the charging process. Figure 5 (e) is a schematic diagram of the evolution mechanism of the negative electrode of the PB||PC composite full cell during the charging process. Detailed Implementation
[0046] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of the present invention is for the purpose of describing particular embodiments only and is not intended to limit the invention.
[0047] Example 1
[0048] This embodiment provides a SiO2@C composite material based on in-situ surface modification, the preparation process of which is as follows:
[0049] 1) Add 1 gram of graphite powder to 20 ml of 2 mol / L H2O2 solution and stir at 60°C for 4 hours. Through the oxidation of H2O2, hydroxyl groups are generated on the graphite surface. Wash the above solution with deionized water and centrifuge 3 times to obtain the graphite matrix.
[0050] 2) Dissolve 8 mL of KH550 silane coupling agent and 1 g of PVP in a mixed solvent (anhydrous ethanol: ultrapure water = 40 mL: 20 mL), add the graphite matrix, and stir with a magnetic stirrer at 60°C for 2 hours to hydrolyze KH550 to promote the chemical grafting reaction. After the reaction is complete, perform solid-liquid separation quickly. Wash the obtained solid phase with anhydrous ethanol at least twice to remove excess silane.
[0051] 3) The solid phase was dried to constant weight in an oven at 100°C, and then heated to 450°C at a heating rate of 5°C / min in an argon atmosphere and held for 4 hours. The resulting powder was cooled to 280°C at a rate of 5°C / min and held for 12 hours to finally form the SiO2@C composite material.
[0052] This embodiment also utilizes the obtained SiO2@C composite material to prepare the corresponding PB||SiO2@C composite full cell, the process of which is as follows:
[0053] Step S1: Mix active PB, acetylene black and PVDF binder in NMP (AR, 99%, Aladdin) solution at a weight ratio of 7:2:1 and stir overnight to obtain positive electrode slurry; coat the positive electrode slurry onto an aluminum foil current collector, then dry it at 80°C for 24 hours, and cut it into circular PB positive electrodes with a diameter of 1.2 cm.
[0054] Step S2: Mix SiO2@C composite material, acetylene black and CMC binder in a mixed solvent (anhydrous ethanol: ultrapure water = 40 mL: 20 mL) at a weight ratio of 8:1:1 to obtain negative electrode slurry; coat the negative electrode slurry onto a copper foil current collector, then dry it at 80°C for 24 hours, and cut it into circular SiO2@C composite negative electrodes with a diameter of 1.2 cm;
[0055] Step S3: Combine the SiO2@C composite negative electrode, PB positive electrode, glass fiber diaphragm and 1M KPF6 / EC:DEC electrolyte to form PB||SiO2@C composite material, and encapsulate it to obtain the final product.
[0056] Comparative Example 1
[0057] This comparative example is exactly the same as Example 1, except that commercial pure graphite was used without any treatment to obtain the PC composite material.
[0058] Furthermore, the present invention also performed relevant electrochemical characterization on various batteries prepared using the composite materials obtained in Example 1 and Comparative Example 1 as negative electrodes, and the results are as follows: Figures 1-5 As shown:
[0059] like Figure 1 As shown in (a), KH550 is used to chemically treat the raw graphite. The hydrolyzed KH550 can combine with oxygen atoms on the graphite surface. The KH550 chemically grafted onto the graphite anode material is then decomposed by subsequent heat treatment to form a uniform SiO2 coating. This coating can effectively regulate the electronic structure of graphite: on the one hand, this layer can generate more active sites and has a relatively high potassium adsorption energy; on the other hand, the SiO2 coating can effectively prevent direct contact between the internal active graphite and the electrolyte, suppress the occurrence of side reactions, and reduce irreversible capacity loss. This suppression effect helps to improve the coulombic efficiency of the battery and improve the overall electrochemical performance. Furthermore, the SiO2 coating also helps to form a thin and uniform high potassium ion conductive SEI film. Therefore, the constructed SiO2@C composite anode exhibits efficient storage and diffusion of potassium within the graphite layer.
[0060] Figure 2 (a) shows the relationship between the DRT function (γ(τ)) and relaxation time (τ) of the SiO2@C composite material obtained based on impedance data. The kinetic processes with relaxation times decreasing from high to low are: charge transfer process (τ> 10). –1 ) and K + Crossing the SEI process (τ<10) –1 The results show that the R of the SiO2@C composite material... SEI and R ct The significant reduction indicates that the SEI of the SiO2@C composite material has high ionic conductivity, promoting interfacial reactions and facilitating rapid ion diffusion in the electrode, which is the reason for its excellent rate capability and cycling performance. Furthermore, as... Figure 2 As shown in (c), the activation energy during the interfacial desolvation / migration reaction is calculated according to the classical Arrhenius law. SiO2-Gr passes through the K0 of the SEI. + The diffusion activation energy is 80.3 kJ·mol⁻¹. -1 This is far lower than the ~99.8 kJ / mol of original graphite. -1 This result is in excellent agreement with the DRT results and determines the ability for rapid charge transfer. Furthermore, to investigate the diffusion kinetics of potassium ions in the SiO2@C composite anode and the PC composite anode during the charging / discharging process, this invention uses 100 mA g... −1 The results were obtained by constant current intermittent titration at a current density as follows: Figure 2As shown in (d), during the discharge process, the SiO2@C composite anode exhibits a smaller overpotential compared to the PC composite anode, indicating that the potassium ion diffusion coefficient (D) is significantly lower. K Enhancement. Correspondingly, as a function of depth of discharge, the SiO2@C composite anode provides a higher DK than the PC composite anode. K Especially from 0.3 V to 0.05 V, this indicates that the potassium diffusion kinetics within the graphite layer are much faster. This is likely due to the increase in electronic conductivity of the PC composite with increasing potassium ion intercalation. To gain a deeper understanding of the potassium storage rate capabilities of the two anode materials, density functional theory (DFT) calculations were performed to investigate the diffusion and adsorption behavior of potassium in the SiO2 and KF structures. Figure 2 (f) shows the diffusion barriers of potassium (K) through SiO2 and KF to evaluate the interfacial K diffusion behavior. The energy barrier for potassium diffusion through the SiO2 layer is only 0.035 eV, much lower than that of the KF layer (0.695 eV). Therefore, the SiO2 modification layer effectively enhances the K diffusion kinetics to achieve an efficient potassium conversion / depotassium process. This result is in good agreement with the high capacity of the SiO2@C composite anode at ultra-high current densities. Furthermore, the adsorption behavior of potassium by SiO2 and KF was calculated. According to the calculation, the formation energy of SiO2 is -2.514 eV, much lower than that of KF (-1.204 eV). The results indicate that SiO2 has a higher affinity for potassium than KF, thus promoting potassium adsorption during potassium conversion. Combined with the above analysis, it is verified that the SiO2 modification layer, with its relatively high potassium adsorption capacity and low diffusion barrier, provides the SiO2@C composite anode with increased active sites, rapid solid-state potassium transfer, and kinetically efficient potassium conversion / depotassium conversion.
[0061] Thanks to the rational design and good conductivity of the SiO2 modification layer, the SiO2@C composite anode exhibits excellent rate performance. For example... Figure 3 As shown in (a), the initial coulombic efficiency of the SiO2@C composite material is significantly improved. Compared to the 71% initial coulombic efficiency of the original PC composite material, the prepared SiO2@C composite material exhibits a high initial coulombic efficiency of 84.1%. This is likely due to the formation of a thin, dense, and stable SEI, thereby reducing irreversible potassium ion consumption. Furthermore, the SiO2@C composite electrode exhibits excellent rate performance at every current density, even at 500 mA g. −1 At a current density, it still has 212.7 mAh g. −1 The high discharge capacity exhibits ultrafast potassium storage reaction kinetics. When the current density returns to 50 mA g... −1Even at 500 mA g, the capacity can still be recovered, indicating that the SiO2@C composite material has significant stability. In stark contrast, the PC composite anode exhibits poor performance at 500 mA g g. −1 The reversible capacity at that time was only 100.1 mA hg−1, which is 34.8% of the initial capacity, far lower than the 74.6% of the SiO2@C composite anode. Figure 3 (c)). This significant difference supports our hypothesis that the SiO2 nanolayers can effectively increase potassium ion adsorption and conductivity, thereby improving charge transfer kinetics and promoting K+ ion exchange. + Migration. It is noteworthy that the cell with the SiO2 nanolayer anode exhibits migration at 100 mA g. −1 The results show a high capacity retention of 70.9% (after 400 cycles), highlighting the excellent cycle stability of the SiO2@C composite anode. In contrast, the battery with the PC composite anode exhibited poor cycle stability during cycling, and at 100 mA g... −1 The battery failed after 50 cycles. Furthermore, during the cycling test, the SiO2@C composite anode maintained a more stable coulombic efficiency of approximately 99.3% compared to the PC composite anode (≈95.6%), further validating the highly robust and reversible potassium conversion / depotassium removal process of the SiO2@C composite anode. This also partially implies the formation of a stable SEI layer on the surface of the SiO2@C composite. The reduction in side reactions on the electrode surface after cycling can be further analyzed using differential capacity plots (dQ / dV), such as... Figure 3 (d) and Figure 3 As shown in (e), the SiO2@C composite material significantly improves the polarization of the battery. Meanwhile, compared to the voltage hysteresis of the PC composite anode, the first and second cycles of the SiO2@C composite material highly overlap, indicating that the SiO2 nanolayer significantly inhibits electrolyte decomposition during SEI formation, which is highly consistent with the high first-cycle coulombic efficiency results.
[0062] Characterizing the interfaces of graphite anodes is crucial for elucidating the relationship between graphite and potassium storage performance. For example... Figure 4 As shown in (b), the SiO2@C composite material exhibited a stronger C signal and a lower F content with increasing etching depth, indicating that the SiO2@C composite material forms a thinner SEI. This is attributed to the SiO2 coating layer on the graphite surface, which prevents the electrolyte from contacting the graphite and effectively inhibits electrolyte decomposition. To further analyze the differences in chemical composition and atomic bonding characteristics between the two anodes, detailed XPS spectral scanning was performed before and after sputtering, as shown in the results. Figure 4As shown in (c), the Si2p spectrum indicates that Si element participates in the construction of SEI. The SEI of the recycled SiO2@C composite anode shows a much higher silicon content than that of the PC composite anode, mainly because SiO2 enhances K diffusion in the SEI.
[0063] like Figure 4 As shown in (d), according to HRTEM studies, an amorphous interface layer with a thickness of ~13.1 nm was observed on the pristine graphite after 20 charge-discharge cycles, consistent with the structure and thickness of the graphite SEI reported previously. Interestingly, the interphase layer (~4.1 nm) observed on the surface of the SiO2@C composite anode is much thinner than that of the pristine graphite. Figure 4 As shown in (e), the TOF-SIMS chemical images reveal the same results as XPS, indicating that the presence of these components in the SEI of the SiO2@C composite synergistically enhances the rapid migration of K at the interface, improves interfacial stability, and avoids continuous electrolyte decomposition and side reactions. These results strongly suggest that the SiO2 modification layer's modulation of the graphite microstructure can produce a high-potassium-conducting SEI film, thereby contributing to the rapid reaction kinetics of potassium conversion / depotassium conversion.
[0064] In summary, this invention modulates the interfacial dynamics of the graphite anode through a SiO2 modification layer. The SiO2 layer successfully improves potassium ion transport efficiency, reduces initial capacity loss, and enhances stability. With the optimized structure, the SiO2@C composite material exhibits a higher affinity for potassium ions, thereby improving rate performance. Furthermore, the SiO2 layer inhibits solvent decomposition, promotes the formation of a thin and uniform solid electrolyte interphase (SEI) film, and lowers the potassium ion migration barrier. Thanks to these significant advantages, the SiO2@C composite anode exhibits high initial coulombic efficiency (84.1%), excellent cycling stability (71% capacity retention after 400 cycles), and high rate performance (213 mAh g⁻¹ capacity at a high current density of 500 mA g⁻¹) in conventional electrolytes. Its practicality was further verified by the PB||SiO2@C composite full cell, which retained up to 90% of its capacity after 600 cycles and showed excellent high-rate performance, with high specific capacity at a current density of 2000 mA g⁻¹.
Claims
1. A method for preparing SiO2@C composite materials based on in-situ surface modification, characterized in that, include: After the carbon material surface is oxidized and cleaned, a carbon matrix is obtained. The silane coupling agent and dispersant are dissolved in a mixed solvent, and a carbon matrix is added to carry out a grafting reaction. After the reaction is completed, the solid-liquid separation and washing are performed to obtain the composite material precursor. The composite material precursor is dried and then SiO2 is grown in situ using a programmed temperature rise method to obtain the final product. The volume mass ratio of the silane coupling agent to the carbon material is 5~10:1mL / g.
2. The method for preparing SiO2@C composite material based on in-situ surface modification according to claim 1, characterized in that: The carbon material is at least one of graphite, graphene, carbon nanotubes, and hard carbon; the surface oxidation treatment is by volume impregnation with an oxidant, the process of which is as follows: under stirring conditions at 50~70℃, the carbon material is completely impregnated in the oxidant for 2~6 hours.
3. The method for preparing SiO2@C composite material based on in-situ surface modification according to claim 2, characterized in that: The oxidant is hydrogen peroxide, with a concentration of 1-3 mol / L; the mass-to-volume ratio of the carbon material to hydrogen peroxide is 1:10-30 g / mL.
4. The method for preparing SiO2@C composite material based on in-situ surface modification according to claim 1, characterized in that: The silane coupling agent is at least one of KH550, KH560, KH580 and A-1100; the dispersant is at least one of PVP, PVA and PMMA; the mixed solvent is composed of anhydrous ethanol and deionized water in a volume ratio of 1 to 3:
1.
5. The method for preparing SiO2@C composite material based on in-situ surface modification according to claim 1, characterized in that: The grafting reaction conditions are: under stirring, the temperature is 50~70℃, and the reaction time is 1~3h; the washing process is: the filter cake is washed with anhydrous ethanol until no silane is present in the washing liquid.
6. The method for preparing SiO2@C composite material based on in-situ surface modification according to claim 1, characterized in that: The drying method is one of vacuum drying, oven drying, and freeze drying; when the drying is oven drying, the conditions are: drying the material at 80~120℃ to constant weight.
7. The method for preparing SiO2@C composite material based on in-situ surface modification according to claim 1, characterized in that: The in-situ growth process of SiO2 is as follows: under a protective atmosphere, the temperature is heated to 400-500℃ at 1-10℃ / min and held for 3-6 hours, then cooled to 250-300℃ at 1-10℃ / min and held for 10-20 hours, and then cooled to room temperature with the furnace.
8. A SiO2@C composite material based on in-situ surface modification, characterized in that: The SiO2@C composite material is prepared by the method according to any one of claims 1 to 7; the SiO2@C composite material comprises a carbon matrix and a SiO2 nanolayer modified in situ on its surface; the thickness of the SiO2 nanolayer is 1 to 10 nm.
9. The application of the SiO2@C composite material based on in-situ surface modification as described in claim 8, characterized in that: This material is used to prepare a potassium-ion secondary battery. The potassium-ion secondary battery includes a positive electrode, a negative electrode containing SiO2@C composite material, a separator, and an electrolyte. The positive electrode includes the following components by weight: 6-8 parts of active PB, 2-3 parts of conductive agent, and 1-2 parts of binder. The negative electrode includes the following components by weight: 7-8 parts of SiO2@C composite material, 1-2 parts of conductive agent, and 1-2 parts of binder.
10. The application of the SiO2@C composite material based on in-situ surface modification according to claim 9, characterized in that: The preparation process of the potassium-ion secondary battery includes: Step S1: Mix the active PB, conductive agent and binder in NMP and stir overnight to obtain a positive electrode slurry. Then coat it onto an aluminum foil current collector, and after drying and cutting, obtain the positive electrode sheet. Step S2: Mix the SiO2@C composite material, conductive agent and binder in an ethanol aqueous solution and stir overnight to obtain a negative electrode slurry. Then coat the slurry onto a copper foil current collector. After drying and cutting, a negative electrode sheet is obtained. Step S3: Assemble and encapsulate the negative electrode, positive electrode, glass fiber separator, and KPF6 electrolyte to obtain the final product.